2011
DOI: 10.1002/ajim.20945
|View full text |Cite
|
Sign up to set email alerts
|

Migrant farmworkers' housing conditions across an agricultural season in North Carolina

Abstract: Background-Several studies have documented poor housing conditions for farmworkers but none has focused on migrant farmworker housing, which is often provided as a condition of employment. Farmworker housing quality is regulated, but little documentation exists of compliance with regulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 21 publications
2
86
0
1
Order By: Relevance
“…Research in NC has consistently found that farmworkers with H-2A visas are more likely to receive pesticide safety training, have better housing and field sanitation conditions, and not experience wage theft. 610 At the same time, farmworkers with H-2A visas remain vulnerable. They generally are allowed to work only for the single employer who recruits them.…”
Section: Introductionmentioning
confidence: 99%
“…Research in NC has consistently found that farmworkers with H-2A visas are more likely to receive pesticide safety training, have better housing and field sanitation conditions, and not experience wage theft. 610 At the same time, farmworkers with H-2A visas remain vulnerable. They generally are allowed to work only for the single employer who recruits them.…”
Section: Introductionmentioning
confidence: 99%
“…24 In addition to work-related exposure, most farmworkers live in substandard housing located near fields. 57 Such housing has been found to contain residues of multiple pesticides that can further expose workers. 8 These residues likely reflect drift or take-home pesticide pathways as workers bring pesticides into their residences, as well as the application of pesticides to try to control pest infestations.…”
Section: Introductionmentioning
confidence: 99%
“…Camps that are hidden from public surveillance increase the probability that this vulnerable population will be forced to live in substandard housing that does not meet the minimum standards of current regulations and that farmworkers will be subject to other forms of crime. 23 New North Carolina legislation that deters community engagement in labor camps by classifying trespassing on agricultural facilities as a Class A1 misdemeanor (G.S. 14---159.12(c)(1)) is an example of a regressive policy.…”
Section: Discussionmentioning
confidence: 99%